Air-blast and ground shockwave parameters, shallow underground blasting, on the ground and buried shallow underground blast-resistant shelters: A review. Issue 1 (March 2022) - Anas, S M; Alam, Mehtab; Umair, Mohammad
Weak political systems and poor governance in certain developing countries are found to have a war-like environment where structures are being targeted by blasts and bombs. Industrial blasts due to frail know-how and mishandlings are also quite common. Recent accidental explosions like that occurred at the Beirut Port, Lebanon (August 2020); ammunition depot in the outskirt of the Ryazan City of Russia (November 2020) are of concern for the safety of adjacent building infrastructure and their users. Such intense loading events cause damage to certain elements of a structure which may result in disproportionate or progressive collapse. It necessitates a clear understanding of the phenomenon of the blast and extreme loads induced out of it, and response of the target structure under such loadings. In this study, the state of research on air-blast and ground shockwave parameters, shallow underground blasting, and on the ground and buried shallow blast-resistant shelters are presented. The phenomenon of the self-Mach-reflection of the explosion, loading parameters and empirical blast models available in the open literature followed by the damage criteria for the buildings subjected to the underground blasting and available peak particle velocity (PPV) prediction models have been discussed. To make the application of advanced materials such as fibrous concrete, ultra-high performance concrete, FRP composites, etc., it is important to comprehend the existing blast/shock-resistant shelters and their response under such loading. The shelters are primarily designed by incorporating features of the materials like high degree of deformability/ductility, use of the shock-isolation panels and the mechanism for controlling crack formations. Finally, conclusions and recommendations for future studies are summarised. This paper presents prospects to engineers, town planners, researchers, policymakers and members of the core drafting sectional committees to understand the phenomenon of the blast and extreme loads induced out of it.